The Pathology of Pemphigus: A Mini-Review - D’Angelis, Christopher A. (North American Journal of Medicine and Science, 2013)
Pemphigus is a rare group of blistering autoimmune diseases that affect the skin and mucous membranes. Variants of pemphigus are now known to be associated with certain medications, underlying malignancy and even an endemic form is well recognized. Following the discovery of the autoimmune basis of pemphigus, specific treatment regimens have made strides in significantly reducing the morbidity and mortality once associated with the disease. Traditional histopathology and tissue based techniques have played a pivotal role in the understanding of pemphigus and in highlighting the diversity within this group of diseases. The examination of skin biopsies by light microscopy and immunofluorescence remains the standard for diagnosis today.